Enhancing marine citizenship as a strategy to promote the reduction of single-use plastics consumption in different cultures - Garcia-Vazquez, Eva; Garcia-Ael, Cristina; Mesa, Maritza Librada Cáceres; Dopico, Eduardo; Rodriguez, Noemi (Frontiers in Marine Science, 2022)
Single-use plastics (SUP) coming from the land represent a large fraction of marine plastic debris that threatens the ocean biota today and are one of the main causes of microplastic pollution. Consumer behavior is essential to stop the use and improper disposal of SUP, replacing plastic with alternative eco-friendly products. For the evident plastic pollution of beaches and seas, marine citizenship, interpreted as the personal responsibility that individuals take for the oceans, could help to reduce SUP use and change to sustainable alternatives. Here we studied SUP consumption behaviors in Spain (n = 585) and Mexico (n = 337) using a multivariate multiple regression approach. Different policies and social norms in the two countries were reflected in reduced SUP use in Mexico compared to Spain and more recycling in Spain than in Mexico. The main reasons for the use of SUP were the lack of alternatives and forgetting reusable goods in the two countries. Feeling responsible for the ocean predicted the intention to use eco-friendly alternatives, while sea frequentation predicted recycling. Gender, age, and education influenced significantly the willingness to use eco-friendly alternatives. From the results of this study, campaigns promoting awareness through increased ocean literacy and marine citizenship—even in regions far from the sea—could promote reductions in SUP consumption, enhancing the use of sustainable alternatives. Those campaigns could be tailored by country, taking into account local policies and habits, gender, age, and educational levels.